TGF-β signaling in lymphatic vascular vessel formation and maintenance - Itoh, Fumiko; Watabe, Tetsuro (Frontiers in Physiology, 2022)
Transforming growth factor (TGF)-β and its family members, including bone morphogenetic proteins (BMPs), nodal proteins, and activins, are implicated in the development and maintenance of various organs. Here, we review its role in the lymphatic vascular system (the secondary vascular system in vertebrates), which plays a crucial role in various physiological and pathological processes, participating in the maintenance of the normal tissue fluid balance, immune cell trafficking, and fatty acid absorption in the gut. The lymphatic system is associated with pathogenesis in multiple diseases, including lymphedema, inflammatory diseases, and tumor metastasis. Lymphatic vessels are composed of lymphatic endothelial cells, which differentiate from blood vascular endothelial cells (BECs). Although TGF-β family signaling is essential for maintaining blood vessel function, little is known about the role of TGF-β in lymphatic homeostasis. Recently, we reported that endothelial-specific depletion of TGF-β signaling affects lymphatic function. These reports suggest that TGF-β signaling in lymphatic endothelial cells maintains the structure of lymphatic vessels and lymphatic homeostasis, and promotes tumor lymphatic metastasis. Suppression of TGF-β signaling in lymphatic endothelial cells may therefore be effective in inhibiting cancer metastasis. We highlight recent advances in understanding the roles of TGF-β signaling in the formation and maintenance of the lymphatic system.